The INCREASING KNOWLEDGE ABOUT EXCLUSIVE BREAST MILK AND BREASTFEEDING - Zulfa Rufaida; Sri Wardini Puji Lestari (MIDWINERSLION : Jurnal Kesehatan STIKes Buleleng, 2021)
The Efforts to increase the use of breast milk (ASI) have been agreed globally. WHO and UNICEF with the Innocenti Declaration (September 1990) and the Summit for children (September 1991) determined that in order to achieve optimal maternal and child health status, all women should be able to only breastfeed until the baby is 4-6 months old (exclusively breastfeeding), give complementary foods to breast milk (MP-ASI) on time and continue to breastfeed until the child is 2 years old. The purpose of this community service is to increase mother's knowledge about exclusive breastfeeding and improve correct breastfeeding skills. The methods used are lecture, discussion, role play and mentoring methods. The targets are third trimester pregnant women and breastfeeding mothers with babies aged 6 months in Pagerngumbuk Village, Kec. Wonoayu Kab. Sidoarjo, the implementation of activities in March - August 2018, The analytical method used is frequency distribution. The results obtained, as many as 20 counseling participants with the results of the means pre test value of 44.5 and post test of 74.75, the result is a significant increase in knowledge of 0.000 with a value of t = - 27.840, and 95% CI between - 31.02 - -26.71 meaning that the effect is strong because it does not pass the number 1; giving treatment can increase 2-3 times knowledge compared to not given. Meanwhile, for breastfeeding assistance, the number of participants was 20 respondents. The counseling participants were enthusiastic about the material presented, active participants in discussion activities with evidence of question feedback, and during role play activities participants actively followed the movements taught by the presenter. There was an increase in knowledge of pregnant women in the third trimester and breastfeeding mothers with babies aged 6 months about exclusive breastfeeding and breastfeeding techniques. Health workers always provide information about exclusive breastfeeding and breastfeeding techniques to pregnant women in the third trimester and breastfeeding mothers with babies aged 6 months with continuity. Efforts to increase the use of breast milk (ASI) have been agreed globally. WHO and UNICEF with the Innocenti Declaration (September 1990) and the Summit for children (September 1991) determined that in order to achieve optimal maternal and child health status, all women should be able to only breastfeed until the baby is 4-6 months old (exclusively breastfeeding), give complementary foods to breast milk (MP-ASI) on time and continue to breastfeed until the child is 2 years old. The purpose of this community service is to increase mother's knowledge about exclusive breastfeeding and improve correct breastfeeding skills. The methods used are lecture, discussion, role play and mentoring methods. The targets are third trimester pregnant women and breastfeeding mothers with babies aged 6 months in Pagerngumbuk Village, Kec. Wonoayu Kab. Sidoarjo, the implementation of activities in March - August 2018, The analytical method used is frequency distribution. The results obtained, as many as 20 counseling participants with the results of the means pre test value of 44.5 and post test of 74.75, the result is a significant increase in knowledge of 0.000 with a value of t = - 27.840, and 95% CI between - 31.02 - -26.71 meaning that the effect is strong because it does not pass the number 1; giving treatment can increase 2-3 times knowledge compared to not given. Meanwhile, for breastfeeding assistance, the number of participants was 20 respondents. The counseling participants were enthusiastic about the material presented, active participants in discussion activities with evidence of question feedback, and during role play activities participants actively followed the movements taught by the presenter. There was an increase in knowledge of pregnant women in the third trimester and breastfeeding mothers with babies aged 6 months about exclusive breastfeeding and breastfeeding techniques. Health workers always provide information about exclusive breastfeeding and breastfeeding techniques to pregnant women in the third trimester and breastfeeding mothers with babies aged 6 months with continuity.